Mechanism of the nonequilibrium phase transition in self-propelled particles with alignment - Ruizhe Yan; Jie Su; Jin Wang (Physical Review Research)
Self-propelled particles with alignment, displaying ordered collective motions such as swarming, can be investigated by the well-known Vicsek model. However, challenges still remain regarding the nature of the associated phase transition. Here, we use the landscape-flux approach combined with the coarse-grained mapping method to reveal the underlying mechanism of the order-disorder nonequilibrium phase transition in Vicsek model systems featuring diverse noise characteristics. It is found that the nonequilibrium flux inside the landscape in the density-alignment degree phase space always rotates counterclockwise, and tends to delocalize or destabilize the point attractor states, providing the dynamical driving force for altering the landscape shape and the system state. Furthermore, the variations in the averaged flux and entropy production rate exhibit pronounced differences across various noise types. This not only helps to reveal the dynamical and thermodynamical mechanisms of the order-disorder transition but also offers a useful tool to recognize the continuity of the transition. Our findings present a perspective for exploring nonequilibrium phase transition behaviors and other collective motions in various complex systems.